A IMPORTÂNCIA DA ASSISTÊNCIA ESTUDANTIL NO COMBATE À EVASÃO NO ENSINO MÉDIO INTEGRADO DO IFSP – CAMPUS REGISTRO - Vasconcelos de Lima Kanashiro, Fernanda (2024)
This article consists of a study unfolding, of an exploratory and descriptive nature, anchored in research that analyzed documentary sources and elements of school evasion in integrated high school at the Federal Institute of São Paulo – IFSP – Registro Campus, through a qualitative approach. Specifically, data relating to the evasion of students from the integrated secondary education of Logistics, Buildings and Mechatronics courses, between 2017 and 2021, available on the Nilo Peçanha Platform. The research identified that student assistance is a determining factor for students to remain in these courses, once the largest number of students who dropped out are concentrated in the lowest income bracket. It is worth noting that student assistance can enable social inclusion through financial aid for food, housing and transportation, among other basic items, and is one of the mechanisms for ensuring quality education for all students.